LAYANAN PUBLIK KESEHATAN (BPJS KESEHATAN DAN PUSKESMAS) - Awaayisyah Ananda Glory; Rara Alfaidah; Khoirunnisa Benny; Jidan Rizkian; Muhamad Ali Akbar; Irvan Arif Kurniawan (Yayasan Nusantara Hasana Berdikari, 2026)
This study examines the implementation of public health services in Indonesia through the synergy of the National Health Insurance program (JKN) administered by BPJS Kesehatan and community health centers (Puskesmas). Using a descriptive-analytical literature review approach, this article analyzes four key dimensions: service accessibility, facility distribution, healthcare workforce equity, and financing fairness. The findings indicate that the integration of BPJS Kesehatan and Puskesmas within the JKN framework has significantly expanded healthcare coverage and increased community visits to health facilities. However, drawing on Julian Tudor Hart’s Equity in Health Service theory (1971), also known as the Inverse Care Law, this study identifies persistent inequities in healthcare access, particularly in remote and underserved areas where infrastructure limitations and healthcare workforce shortages remain critical challenges. Digital innovations such as the Mobile JKN application, SIMPUS, and SATUSEHAT have broadened access by reducing barriers of time and distance, yet the digital divide risks creating new forms of inequity. Furthermore, low compliance with insurance premiums among informal sector workers threatens the sustainability of the gotong royong financing principle. This study concludes that while BPJS-Puskesmas synergy has advanced universal health coverage, strategic policy interventions are urgently needed to achieve substantive equity in health service quality and accessibility across Indonesia.